Quality of work life among employees in a manufacturing sector / Nur Lyana Farhana Mohd Nasir - Mohd Nasir, Nur Lyana Farhana (2014)
This research conducted to find out what can be done to improve employee perceptions of their quality of work life. In this research, the researcher has been test on nine factors that deemed related to The Quality of Work Life among the employees in Isuzu Hicom Malaysia Sdn Bhd. The factors are Benefit Received, Work Culture, Safety & Health Working Conditions, Work Hours, Supervisions, Trade Unions, Work & Family Matters, Job Levels and Employee Satisfaction. To identify which factor that most significant to the level of The Quality of Work Life among the employees in Isuzu Hicom Malaysia Sdn Bhd, the data will be collected. The research instrument that has been used is questionnaire. 85 sets of questionnaires had been distributed to the employees in five different departments which are Human Resources & Management, Finance, Purchasing, Procurement and Maintenance. At the end of this research, the researcher will conclude all the research and give some recommendation for further researcher.